Penerapan Pendekatan Culturally Responsive Teaching Berbantuan Flashcard untuk Meningkatkan Keterampilan Menulis di Sekolah Dasar - Muzdalifah, Iyut; Mintohari, Mintohari; Oktania, Mega Wahyu; Masruroh, Intan (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The purpose of this study was to improve the simple writing skills of grade II elementary school students by using a culturally responsive teaching (CRT) approach assisted by flashcard media. The research was conducted in class II-B at SD Negeri Jambangan I/413 Surabaya, involving 32 students. The study utilized classroom action research with the four steps of the Kemmis and McTaggart model: planning, action, observation, and reflection. The data were compiled through learning result sheets and field notes. The study's findings demonstrated that the average score for basic writing abilities had increased from 45 in the pre-action period to 63 in cycle I and 79 in cycle II. The percentage of students achieving learning outcomes improved from 9% in the pre-action phase to 53% in cycle I and 89% in cycle II. It was concluded that culturally responsive teaching assisted by flashcard media could improve simple writing skills in Indonesian subjects in elementary schools through engaging, culture-based learning activities and the support of images to enhance students' understanding and writing abilities.